Cerebrospinal fluid features in adults with enteroviral nervous system infection. (March 2018) - Ahlbrecht, Jonas; Hillebrand, Lilly Katrin; Schwenkenbecher, Philipp; Ganzenmueller, Tina; Heim, Albert; Wurster, Ulrich; Stangel, Martin; Sühs, Kurt-Wolfram; Skripuletz, Thomas
Highlights: The cerebrospinal fluid (CSF) cell count was normal in 15% of all patients. Patients with normal CSF cell counts were older and less frequently had meningitis. PCR for enteroviruses may be useful in suspected central nervous system (CNS) infections without pleocytosis. Enteroviral CNS infections can manifest in the form of isolated cranial nerve involvement. Abstract: Objectives: The aim of this study was to investigate the clinical and laboratory features of adults with nervous system infections caused by enteroviruses, with special emphasis on cerebrospinal fluid (CSF). Methods: The data of 46 patients who were PCR-positive for enteroviruses in the CSF between 2002 and 2017 were evaluated. Results: Meningitis was the most common clinical manifestation (89%), followed by encephalitis (7%) and isolated cranial nerve involvement (4%). Twenty percent of patients reported a sudden onset of severe headache that led to the initial suspected diagnosis of subarachnoid haemorrhage. General signs of infection, such as fever, elevated C-reactive protein, and an elevated white blood cell count, were found in only 61%. Most patients exhibited consistent inflammatory CSF changes, with elevated cell counts (85%) and blood–CSF barrier dysfunction (83%). Patients with normal CSF cell counts were significantly older, less frequently presented with meningitis, and exhibited lower peripheral white blood cell counts. Sequencing revealed species Enterovirus B in all patients, with most sequences related to echovirus 30. Conclusions: The absence of CSF pleocytosis, isolated cranial nerve involvement, and only infrequent general signs of infection may impede the diagnosis of enteroviral nervous system infections. A thorough CSF analysis including PCR is essential for a reliable diagnosis.